Phase III trial of postoperative cisplatin, interferon alpha-2b, and 5-FU combined with external radiation treatment versus 5-FU alone for patients with resected pancreatic adenocarcinoma - CapRI: study protocol (ISRCTN62866759) - Knaebel, Hanns-Peter; Märten, Angela; Schmidt, Jan; Hoffmann, Katrin; Seiler, Christoph; Lindel, Katja; Schmitz-Winnenthal, Friedrich Hubertus; Fritz, Stefan; Herrmann, Thomas; Goldschmidt, Hartmut; Krempien, Robert; Mansmann, Ulrich; et al. (BMC cancer, 2005)
After surgical intervention with curative intention in specialised centres the five-year survival of patients with carcinoma of the exocrine pancreas is only 15%. The ESPAC-1 trial showed an increased five-year survival of 21% achieved with adjuvant chemotherapy. Investigators from the Virginia Mason Clinic have reported a 5-year survival rate of 55% in a phase II trial evaluating adjuvant chemotherapy, immunotherapy and external-beam radiation
Gesehen am 04.02.2022